Study of 4C Components the Avaikability at Physics Worksheets of Senior High School Grade XII in Pesisir Selatan - Anisa Meysi Wardi; - Hamdi; Renol Afrizon; Putri Dwi Sundari; Yenni Darvina (Universitas Negeri Padang, 2021)
The 2013 curriculum requires teachers to encourage students to be able the 21 st century skills consist critical thinking, creativ thinking, communicaton, and collaboratively. To achieve this, teacher must practice using learning strategies with an orientation to train students to be able have 4C skills. This relates to the learning component that must be prepared by the teacher such as teaching materials. The aim of research was conducted to study the availability of the 4C component at physics worksheets of senior high school for XII. The population of data in this study were physics worksheets class XII made by teacher.The samples in this research are fourth Physics worksheets made by physics teacher. The data in this study were taken using physics worksheets presentation analysis instrument with the data analysis technique is a content study and data collection techniques through documentation studies. Based on the analysis result, it can be concluded the analysis of the Physics Worsheets at Senior High School for XII related to availability of the 4C component shows that physics worksheets who obtained a percentage with the fulfillment of the indicator on the highest 4C component is critical thinking indicators obtained a score 59% with category enough facilitated and the lower is collaboration get a score 42,71%.